FREQUENCY OF CANALS IN PERMANENT MAXILLARY SECOND MOLAR ON THE BASIS OF CLINICAL AND RADIOGRAPHIC PARAMETERS (The Research of Medical Science Review, 2025)
Endodontic treatment has a major and productive role in teeth conservation and maintenance in modern dentistry. Endodontic treatment also called root canal treatment (RCT), is the procedure in which the diseased or damaged pulp (core) of a tooth is removed and the inside areas (the pulp chamber and root canals) are filled and sealed. Permanent molars including maxillary 2 nd molars are the most common teeth requiring root canal treatment. Maxillary 1 st and 2 nd molars are among the most difficult teeth for endodontic treatment due to their complex root canal system. Shortage of knowledge regarding root canal anatomy and its variations in configuration may result in numerous root canal treatment failures. The objective of this study was to determine the frequency of canals in permanent maxillary second molar on the basis of clinical and radiographic parameters. A total of 120 subjects were examined. Two detection procedures, clinical and radiographical were used in patients scheduled for endodontic treatment in maxillary second molar. Two pre-operative radiographs with different angulations were taken and access cavity was prepared after administration of local anaesthesia and rubber dam isolation. Canals were first located with DG-16 explorer using magnifying dental loupes and then negotiated with size 10 K file. A third periapical radiograph was taken with the files placed in the negotiated root canals to confirm their presence. Out of the 120 teeth 16 (13.3%) teeth had two canals, 101(84.2%) teeth had three canals, and 3(2.5%) teeth had four canals. Age-wise analysis of the frequency of different canals showed that prevalence of molars with three canals was significantly higher in the subjects with age between 31 and 40 years. To summarize, the study noted four morphological variations in the root canal configuration of Maxillary second molar teeth in Pakistani subpopulation. Hence, while executing the endodontic treatment in the maxillary second molars a thorough assessment of the root canal system should be carried out.